SEMANTIK TEKS AKAD NIKAH DALAM TEORI DAN PRAKTIK - Subaidi; Subyanto (Fakultas Syariah dan Ekonomi Islam, Universitas Ibrahimy, 2021)
The marriage contract has the meaning to hold a marriage as an agreement to marry as a form of acceptance. Basically the marriage contract couldtake using any language that shows a desire, and can be understood by the parts and also can be understood by the witnesses. Fiqh scholars agreed regarding the use of non-Arabic languages in marriage contracts as long as both or one of the two parts could not understand Arabic and the translation of the marriage contract text from Arabic into Indonesian is in accordance with Arabic grammatical rules.